Factors that Affect the Well-Being of Mustahik in the Utilization of Productive Zakat Laznas LMI Malang - Ahmad Bay Dzukri; Susilo (Islamic Economics and finance in Focus, 2025)
This article aims to analyze the influence of factors such as type of business, length of effort, work ethic and assistance on the well-being of mustahik in the utilization of zakat at LMI Malang. This study is a quantitative research using a questionnaire using a likert scale and a method applied using multiple linear regression analysis with the help of the SPSS application. There was a sample of 50 respondents consisting of 24 male respondents and 26 female respondents.  The results of the study were obtained that the factors of business type, length of business, work ethic, and mentoring have a significant influence on the welfare of mustahik in the utilization of zakat at LAZNAS LMI Malang. As for all of these architectural factors, the type of business, length of business, work ethic, and mentoring explained the influence of 29% on the welfare of the mustahik lAZNAS LMI Malang